Biophysical properties of Sugarcane Mosaic Virus (SCMV) and its management - Ali, Amjad; Zeshan, Muhammad Ahmad; Iftikhar, Yasir; Ghani, Muhammad Usman; Anjum, Muhammad Adeel; Amin, Muhammad (Journal of Pure and Applied Agriculture, 2023)
Abstract: The world human population has continued to increase over the years, this has affected availability and shorten supply of food. Food security challenge is bound to happen as the world human population is expected to reach 9 billion by the year 2050 if food production rate did not double its current production rate. The problem is compounded by the reduction in area of arable land available for farming and food production due to urbanization, salinity, land degradation, desertification, natural and man-made disasters, and climate change. The crop production and food security are under threat from these factors. To address challenges, a call for the development of improved new varieties of crop plants that can give more yield under abiotic and biotic stresses is inevitable; and can be achieved through improving various